It looks like you're new here. If you want to get involved, click one of these buttons!

- 30.2K All Categories
- 25.6K LSAT
- 15.8K General
- 26 Sage Advice
- 4.6K Logical Reasoning
- 1.2K Reading Comprehension
- 1.6K Logic Games
- 65 Podcasts
- 186 Webinars
- 5 Scholarships
- 191 Test Center Reviews
- 1.7K Study Groups
- 98 Study Guides/Cheat Sheets
- 2.2K Specific LSAT Dates
- 20 June 2023 LSAT
- 6 April 2023 LSAT
- 9 February 2023 LSAT
- 25 January 2023 LSAT
- 4.6K Not LSAT
- 3.8K Law School Admissions
- 8 Law School Explained
- 11 Forum Rules
- 514 Technical Problems
- 271 Off-topic

2 Likes

Peter
Free Trial Member

It really helps me understand the concepts of assumption questions by looking at it formally. Could someone check my logic?

So say we have a premise (B->C) and we have the conclusion (A->C) and say we have the two question stems

Question stem 1: Which one of the following, if assumed, ALLOWS the conclusion to be properly drawn?

Question stem 2: Which one of the following assumptions is REQUIRED for the conclusion to be properly drawn?

For question stem 1, we're looking for a sufficient assumption. Is that just saying something like

___ (and) (B->C) -> (A->C)

so in this case (A->B) would be the obvious sufficient assumption that fills the blank?

For question stem 2, we're looking for the necessary assumption. Is that saying

(B->C) (and) (A->C) -> ___

where the necessary assumption fills in the blank? Something about this doesn't seem quite right.

So say we have a premise (B->C) and we have the conclusion (A->C) and say we have the two question stems

Question stem 1: Which one of the following, if assumed, ALLOWS the conclusion to be properly drawn?

Question stem 2: Which one of the following assumptions is REQUIRED for the conclusion to be properly drawn?

For question stem 1, we're looking for a sufficient assumption. Is that just saying something like

___ (and) (B->C) -> (A->C)

so in this case (A->B) would be the obvious sufficient assumption that fills the blank?

For question stem 2, we're looking for the necessary assumption. Is that saying

(B->C) (and) (A->C) -> ___

where the necessary assumption fills in the blank? Something about this doesn't seem quite right.

## Comments

You're on the money for the sufficient assumption question (stem 1). I'd emphasize

"ifassumed" as opposed to "allows".You're also right to feel some unease about stem 2, the necessary assumption question stem. Necessary assumptions are assumptions that must be true if the argument is valid. Please note that "the argument is valid" is different from "the premise is true and the conclusion is true." The difference is that for the argument to be valid the conclusion must derive its truth from the premises. In LSAT world, anyway, that's the case. So necessary assumption questions are asking us to find an assumption that must be true so that the existing premises still have a shot of forming (with other assumptions and the existing conclusion) a valid argument. In other words, if the necessary assumption is false, then existing premises will not be able to support ("lend truth to") the conclusion.

Instead of (B-->C) (and) (A-->C) --> necessary assumption answer choice

It should be: [(___) (and) (B-->C) --> (A-->C)] --> necessary assumption answer choice

As it turns out, sometimes, the sufficient assumption is also the necessary assumption. Often, that happens in simple arguments like the one you gave as an example.

B-->C

_______

A-->C

It's evident that A-->B and B-->C implies A-->C. That A-->B is a sufficient assumption is therefore evident.

It's harder to see why A-->B is also a necessary assumption. Consider if A wasn't sufficient for B. In other words, A and not B. Then, B-->C becomes useless to support A-->C. Sure, it could be that A-->X and X-->C, therefore, A-->C. But that's a brand new argument, an argument in which B-->C played no role in supporting A-->C. So if we deny A-->B, then there's no way for B-->C to get us to A-->C. That's why A-->B is also a necessary assumption for that particular argument.

For enrolled students, relevant lessons below:

http://7sage.com/lesson/how-to-find-the-sufficient-assumption/

http://7sage.com/lesson/how-to-find-necessary-assumptions/

http://7sage.com/lesson/advanced-negate-all-statements/

Would it be something like {A (and) (A->B) (and) (B->C) (and) C} -> (A->C)

where A is sufficient but not necessary, since (not) A wouldn't wreck the argument?

(A->B), (B->C) are both sufficient and necessary

C is not sufficient but necessary, (not) C would wreck the argument?

I suppose in the example we had, you could say "Well, A-->B isn't really necessary. All we need is just "It's possible that 'A-->B'" I don't think the LSAT gets that deep into what is "really necessary."

In the example you gave

{A (and) (A->B) (and) (B->C) (and) C} -> (A->C)

A and C in the premises are superfluous premises, neither necessary nor sufficient. Your conclusion is conditional, i.e., if A then C. So we don't need to "trigger" A or C. All men are mortal, all mortals are silly sometimes. Therefore, all men are silly sometimes. We don't need to talk about a particular man.

Most Necessary Assumption questions are not formal, I believe.